2019
DOI: 10.1111/medu.13907
|View full text |Cite
|
Sign up to set email alerts
|

Experience‐based learning: junior medical students’ reflections on end‐of‐life care

Abstract: Context Experience‐based learning may contribute to confidence, competence and professional identity; early experiences may be particularly formative. This study explored how pre‐clinical students make sense of their participation in the provision of end‐of‐life care within community settings. Methods We performed dialogic narrative analysis on essays written by junior medical students in New Zealand. Students had reflected on their participation as assistant caregivers in nursing homes, contributing to the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 33 publications
2
20
0
Order By: Relevance
“…Articles that focused on values embedded within the profession included a study by Cope et al, 59 which looked at the expectations of surgery trainees who endorsed being driven by ‘perfectionism’, which made them feel ‘neurotic’. Others focused on how our institutions play a role in the construction of a professional identity, 65,113 including through the use of structured training programmes for students, residents and faculty members, 46,60‐62,100,104,114 physical spaces for trainees, 115 call modalities, 74 and opportunities for narrative writing 67,73 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Articles that focused on values embedded within the profession included a study by Cope et al, 59 which looked at the expectations of surgery trainees who endorsed being driven by ‘perfectionism’, which made them feel ‘neurotic’. Others focused on how our institutions play a role in the construction of a professional identity, 65,113 including through the use of structured training programmes for students, residents and faculty members, 46,60‐62,100,104,114 physical spaces for trainees, 115 call modalities, 74 and opportunities for narrative writing 67,73 …”
Section: Resultsmentioning
confidence: 99%
“…Grounded theory (n = 17) was cited as the most commonly used methodology, which is appropriate in contexts in which researchers believe divergent epistemologies exist 69 . However, quite a few studies did not mention their choice of methodology (n = 11) and reported vague terms such as ‘inductive analysis’ or ‘open coding’ to describe the analytical work 45,51,52,54,55,58,63‐65,70‐81 . Studies included various contexts previously identified in health education research 82 (eg, longitudinal clerkships, social media, patient care, dual professions, etc.)…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Reflection is considered to be a key component of experiential learning, where there is an ongoing cycle of experience, analysis, theoretical review and planning for further action. 7 Reflection in medical education is thus largely focused on improving students' learning and on providing initial appreciation of the complexity and nuances of health professionals' work. Ideally, such reflection leads to 'transformative learning' where students gain insights into their own attitudes, ideas and roles in health care delivery.…”
Section: … Critical Reflection Can Also Help Students Examine and Crimentioning
confidence: 99%